Plant Collections of Bali Botanic Garden Potentially Used As Organic Pesticides - Wibawa, I Putu Agus Hendra; Priyadi, Arief (Proceeding International Conference on Global Resource Conservation, 2013)
Along with society awareness of the importance of healthy life, demand of agricultural products which are pesticide residues free has been increasing. Recently, efforts to control plant pests and diseases by farmers have been relied on synthetic pesticides. Utilization of this kinds of pesticides results in various diseases such as cancer, fetal defects, infertility, liver diseases, and so on.Â  One of the alternatives which can be chosen to minimize those negative effects is using organic pesticides. Its ingredients are organic compounds which easily degraded, do not pollute the environment and relative safe for humans and livestock because its residues are degradable. Indonesia is one of countries with biggest biodiversity in the world, so it has great opportunities to produce organic pesticides. Bali Botanic Garden (BBG) is a government institution which plays role to conserve various kinds of plants from their natural habitats, especially the threatened species. This activity was aimed at knowing how many plant collections in BBG which have potency as organic pesticides and their specific functions whether as fungicides, insecticides, bactericides, rodenticides, nematicides, molluscicides, or fish poisons. The results show that there were 23 plants which have potency as organic pesticides. From that group, 22 kinds act as insecticides, 7 as fungicides, 5 as nematicides, 3 as molluscicides, rodenticides, fish poisons (pissicides), and bactericides respectively.Keywords: organic pesticides, Bali Botanic Garden, plant collectionsÂ Keywords: organic pesticides, Bali Botanic Garden, plant collections